Change of glucometabolic activity per PSMA expression predicts survival in mCRPC patients non-responding to PSMA radioligand therapy: introducing a novel dual imaging biomarker - Burgard, Caroline; Engler, Jakob; Blickle, Arne; Bartholomä, Mark; Maus, Stephan; Schaefer-Schuler, Andrea; Khreish, Fadi; Ezziddin, Samer; Rosar, Florian (Frontiers in Medicine, 2024)
Purpose: The value of [ 18 F]fluorodeoxyglucose ([ 18 F]FDG) PET/CT in monitoring prostate-specific membrane antigen (PSMA) targeted radioligand therapy (RLT) is still unclear. The aim of this study was to identify appropriate prognostic dynamic parameters derived from baseline and follow-up [ 18 F]FDG and dual [ 18 F]FDG/[ 68 Ga]Ga-PSMA-11 PET/CT for monitoring early non-responding mCRPC patients undergoing PSMA-RLT. Methods: Twenty-three mCRPC patients of a prospective registry (NCT04833517), who were treated with [ 177 Lu]Lu-PSMA-617 RLT and classified as early nonresponders were included in this study. All patients received dual PET/CT imaging with [ 18 F]FDG and [ 68 Ga]Ga-PSMA-11 at baseline and after median two cycles of RLT. We tested potential biomarkers representing the 'change of glucometabolic activity (cGA)' and 'change of glucometabolic activity in relation to PSMA expression (cGAP)' composed of established parameters on [ 18 F]FDG PET/CT as SUVmax, cumulative SUV of five lesions (SUV5), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) and its corresponding parameters on [ 68 Ga]Ga-PSMA-11 PET/CT, respectively, for association with overall survival (OS).Results: Kaplan-Meier analyses showed no significant association with OS for each tested cGA (cGASUVmax p = 0.904, cGASUV5, p = 0.747 cGAMTV p = 0.682 and cGATLG p = 0.700), likewise the dual imaging biomarkers cGAPSUVmax (p = 0.136), cGAPSUV5 (p = 0.097), and cGAPTV (p= 0.113) failed significance. In contrast, cGAPTL, which is based on TLG and total lesion PSMA (TLP) showed a significant association with OS (p = 0.004). Low cGAPTL (cut-off 0.7) was associated with significant longer survival (17.6 vs. 12.9 months).The novel biomarker cGAPTL, which represents the temporal change of whole-body TLG normalized by TLP, predicts overall survival in the challenging cohort of patients non-responding to PSMA-RLT.